2011
DOI: 10.1126/science.1194732
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Basis of Intuitive Best Next-Move Generation in Board Game Experts

Abstract: The superior capability of cognitive experts largely depends on quick automatic processes. To reveal their neural bases, we used functional magnetic resonance imaging to study brain activity of professional and amateur players in a board game named shogi. We found two activations specific to professionals: one in the precuneus of the parietal lobe during perception of board patterns, and the other in the caudate nucleus of the basal ganglia during quick generation of the best next move. Activities at these two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(111 citation statements)
references
References 41 publications
7
103
0
1
Order By: Relevance
“…We predicted that Korean participants would show more enhanced activity in brain regions associated with intuitive and approximation processes, while their American counterparts would show stronger activity in the regions associated with reasoning and cognitive processes. In fact, a significant main effect of the group factor was found in the insula, putamen, postcentral sulcus, ACC, and SFG, which are associated with either intuitive, approximation, or reasoning process [38][39][40][41][42][43][44][45][46][47][48]. The result of the ANOVA of the main effect of the dilemma type also successfully replicated the previous fMRI investigation of moral functioning conducted by Greene et al [15].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We predicted that Korean participants would show more enhanced activity in brain regions associated with intuitive and approximation processes, while their American counterparts would show stronger activity in the regions associated with reasoning and cognitive processes. In fact, a significant main effect of the group factor was found in the insula, putamen, postcentral sulcus, ACC, and SFG, which are associated with either intuitive, approximation, or reasoning process [38][39][40][41][42][43][44][45][46][47][48]. The result of the ANOVA of the main effect of the dilemma type also successfully replicated the previous fMRI investigation of moral functioning conducted by Greene et al [15].…”
Section: Discussionsupporting
confidence: 78%
“…Given previous studies of the cognitive functional role of the putamen, the activity in this area is significantly associated with intuitive social decision making and behavioral processes [38,39]. In addition, a previous study suggested that the putamen is associated with automatic emotional responses and processes, in particular, negative emotions, such as hate and disgust [49].…”
Section: Discussionmentioning
confidence: 99%
“…Chess experts, who also depend on quick automatized responses like expert musicians, also manifested a reduced volume in the caudate nucleus (Duan et al 2012). This phenomenon also manifested in other board games and skills (Wan et al 2011;Poldrack et al 2005). In accordance, we show for the first time a stepwise GMD decrease in the caudate nucleus with musical aptitude.…”
Section: Negative Effects Of Expertisesupporting
confidence: 70%
“…Several neuroimaging studies have revealed that the playing of board games such as Go or chess is related to executive function and problem solving skills 21,22. Chen et al (2003) investigated the neural basis of Go using functional magnetic resonance imaging and observed enhanced activations in cortical areas of the dorsal prefrontal, parietal, occipital, posterior temporal, and primary somatosensory and motor areas.…”
Section: Introductionmentioning
confidence: 99%